2004 IEEE International Conference on Acoustics, Speech, and Signal Processing
DOI: 10.1109/icassp.2004.1326752
|View full text |Cite
|
Sign up to set email alerts
|

Speech processing for hearing aids for moderate bilateral sensorineural hearing loss

Abstract: Binaural dichotic presentation can be used for reducing the effects of increased temporal and spectral masking associated with sensorineural loss and for improving speech perception by persons with moderate bilateral loss. Speech processing schemes based on adjustable gain filtering, spectral splitting with perceptually balanced comb filters, temporal splitting with trapezoidal fading and inter-aural switching period of 20 and 40 ms, and combined splitting with cyclically swept comb filters with cycle time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[5]. Since the requirements on the hearing aid vary patient to patient, there are several issues which need further attentions in order to provide better quality from user point of view, such as:…”
Section: Introductionmentioning
confidence: 99%
“…[5]. Since the requirements on the hearing aid vary patient to patient, there are several issues which need further attentions in order to provide better quality from user point of view, such as:…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported on binaural dichotic presentation, using a pair of comb filters with complementary magnitude responses for spectral splitting, to reduce the effects of spectral masking for persons with moderate bilateral sensorineural hearing impairment (Lyregaard 1982;Lunner et al 1993;Chaudhari and Pandey 1998;Cheeran and Pandey 2004;Kulkarni et al 2006). For monaural hearing, effect of increased spectral masking may be reduced by multi-band frequency compression.…”
mentioning
confidence: 96%